PENGARUH PEMBERIAN BEE POLLEN TERHADAP PEMULIHAN KADAR HEMOGLOBIN SETELAH 1 JAM LATIHAN SUBMAKSIMAL - Pangestu, Trio Aji; Bawono, Mokhamad; Irawan, Roy (Kesehatan Olahraga, 2024)
The use of herbal medicine as a health supplement is increasingly popular among athletes. One such supplement is Bee Pollen, known for its stamina-enhancing properties. Athletes often seek ways to maintain their physical condition, and this study aimed to investigate the effects of Bee Pollen supplements on hemoglobin level recovery after 1 hour of submaximal exercise. This quantitative descriptive research involved undergraduate students from the Sports Science class of 2021, with a sample of 20 individuals selected through purposive sampling. Data analysis included descriptive tests, normality tests, homogeneity tests, and hypothesis tests (Anova Repeated Measures). The results indicated a significant effect of Bee Pollen supplementation (520 mg) on hemoglobin level recovery in the experimental group compared to the control group. The experimental group showed a 9.9% increase in hemoglobin levels, while the control group only had a 1.05% increase. Therefore, Bee Pollen supplements (520 mg) can expedite the recovery of hemoglobin levels after submaximal exercise.